Firefly wedding. 5 - Tachibana, Oreco (Firefly Wedding, 2026)
Satoko dreams of marrying a noble but can't escape the assassin who has her within his sights. Afflicted with a heart condition, Meiji-era noblewoman Satoko is determined to secure a marriage that will benefit her family before she dies. But before she can realize her goal, she's targeted by a mysterious assassin named Shinpei. In a last-ditch effort to save her life, Satoko asks her would-be murderer to marry her. Her proposal isn't sincere, but unfortunately for her, Shinpei loves as intensely as he kills. Can Satoko find a way to break the engagement without losing her life? Satoko and Shinpei head into town on an errand for Asagiri, the prostitute who rules Goddess Island from the shadows. The more time the two of them spend alone together, the more deeply Satoko comes to understand Shinpei, and her feelings for him blossom. Meanwhile, fueled by jealousy and his duty as an attendant, Kotaro makes his move and tries to pull Satoko away from the assassin by force.